Comparing the social signaling behavior of humpback whales in three group types on the Hawaiian breeding grounds using acoustic tags - Carvalho, Jessica; Lammers, Marc O.; Indeck, Katherine L.; Pack, Adam A.; Castilho, Rita (Frontiers in Remote Sensing, 2022)
Humpback whales (Megaptera novaeangliae) are exceptionally vocal among baleen whale species. While extensive research has been conducted on humpback whale songs, gaps remain in our understanding of other forms of communication, particularly non-song calls. Here, we compare the spectral features and temporal parameters of non-song calls recorded from AcousondeTM tagged humpback whales in three commonly observed group types in the breeding grounds: adult dyads (N = 3), singly escorted mother-calf pairs (N = 4), and competitive groups (N = 4). Recordings were collected off Maui, Hawai’i during the winter breeding seasons of 2019–2021. Individual calls were identified based on visual and aural inspection of spectrograms using Raven Pro 1.6 software, with a total of 842 calls isolated from 47.6 h of acoustic recordings. Competitive groups produced the most calls (N = 358); however, after adjusting for the differences in recording hours and the number of individuals, the call rate (calls/hour/whale) was not significantly different between group compositions. The temporal parameters and frequency measures of calls did not vary significantly across the groups. However, interesting patterns of calling behavior were observed (e.g., competitive groups had the shortest inter-call intervals and the highest frequency calls, and escorted mother-calf pairs had the longest inter-call intervals) and it is possible the lack of statistical significance could be attributed to the small sample size of tag deployments. This study provides new insights into humpback whale vocal communication behavior in the Hawaiian Islands breeding grounds.